The failure of the United States coercive diplomacy in the era of President Donald Trump: Turkey’s persistence in buying S-400 - Febry Triantama; Cancera Triane Berliana; Muhammad Yusril I'za (Faculty of Social and Political Science, Universitas Airlangga, 2022)
Turkey decided to acquire the S-400 air defense system from Russia in 2017. This decision puts Turkey in the shadow of the United States’ coercive diplomacy through the CAATSA instrument. However, Turkey showed its persistence, as evidenced by the arrival of the S-400 in Turkey in 2019. This study aims to find out the reason for Turkey’s persistence using the concept of coercive diplomacy and descriptive-analytical methods. This article concludes that the reason for Turkey’s persistence in buying S-400 was the implementation of United States coercive diplomacy through CAATSA that tends to be “half-hearted”. “Half-hearted” coercive diplomacy done by the United States made all three strategies for a successful and effective coercive diplomacy cannot be achieved. First, the demands and threats presented did not have strong credibility and legitimacy. Second, the Turkish government’s lack of urgency in complying with the US demands contributed to the cause of such persistence. Finally, the absence of time pressure is also important to assure a successful and effective coercive diplomacy.